Incidence of Chronic Kidney Disease Stage 5 Hemodialysis Patients in the Month of December 2023 – A Snapshot survey - Basit, Bilal; Sabir, Omer (Pakistan Journal of Kidney Diseases, 2024)
Introduction: Chronic kidney disease progressing to hemodialysis is a significant health care burden. Since no formal registry including all incident hemodialysis patients is nonexistent. This snapshot survey was conducted to document new enrolling patients in the hemodialysis units across Pakistan. Methods: a simple survey was devised to enquire about the new enrollments for maintenance dialysis in each unit. Age and gender and geographical location of the patients was asked. Results: A total of 995 patients were enrolled in different dialysis units during the month of December 2023. Majority were males and in the age range less than 40 years. Conclusion: A significant number of patients are being enrolled for maintenance dialysis each month, highlighting the increasing burden of CKD patients progressing to ESKD. Larger studies and national hemodialysis registry may help in understanding the actual burden on health budget.